Opportunities and Challenges of Tourism Industry in the Context of Visit Nepal 2020 - Badal, BP; Kharel, Suman (Tribhuvan University Journal, 2019)
Welcoming two million tourists in 2020, is itself a challenge and the challenge from another side is a great opportunity for Nepalese tourism development. Only tourism can transform the nation because other sector of economy requires extensive capital and skillful human resource. Nepal cannot compete with India in Agricultural Production and with China in other industrial productions. Nation’s investment in Agriculture and Industries are in high risks. At this crucial juncture of time Nepal government has announced visit Nepal 2020, which could be a milestone of Nepalese Economic Development. To analyze the challenges and opportunities to welcome 2 million tourists in 2020 the study has been designed. Tourism is a social phenomenon that promotes the movement of visitors to a region or destination in the world with certain natural or artificial features aimed to leisure and rest. Methodologically, it is a qualitative descriptive analysis of available secondary information on Nepalese tourism industry and academia. The method analyzes entire facts qualitatively and interprets the meaning of tourism information. The tourism industry’s viability is based on its natural and cultural environment. The environment encompasses air, land, water, art, history, architect, festivals, and hospitability of people. The foreign tourists and excursionists’ primary interest in Nepal is to study its culture and nature not dust, dirt, and mismanagement of roads etc. Mayors of local governments must be aware on these issues. Nepal’s unique form of musical expression and cultural vibes are becoming lost resulting in cultural dilution. Accessibilities and identification of tourist circuit along with standard food and well accommodation facilities are prior for tourism development for visit Nepal 2020.